Energy storage management in a near zero energy building using Li-ion, lead-acid, flywheel, and photovoltaic systems with TRNSYS simulation - Haddad, Masoud; Javani, Nader; Rezaie, Behnaz (ELSEVIER, 2025)
In the present study, a dynamic analysis of a photovoltaic (PV) system integrated with two electrochemical storage systems, lithium-ion and lead acid batteries, and a flywheel mechanical energy storage system is investigated. Simulations are carried out using TRNSYS software. The considered PV system is installed at Pittsburgh University at Bradford in Pennsylvania, USA. A one-week-long data measurement is obtained for the installed PV system modules. The energy and exergy analyses are employed to evaluate the PV system efficiency. The average energy efficiency of the panel is calculated as 17.3 %, with a peak energy efficiency of 20.6 %. Furthermore, the average daily efficiency of the panel is calculated as 18.6 %, with the highest exergy efficiency of 22.2 %. The State Of Charge (SoC) variation is simulated dynamically, and the fluctuations are studied over the observed period. The inertial weight method is employed to achieve the optimal positioning of panels to maximize power output. The optimum angle of 6 degrees is obtained, which is consistent with locally installed panels. In addition, the study incorporates an economic analysis to estimate the total lifecycle cost of each storage system over a 15-year period, including initial investment, replacement, and operation and maintenance costs. A general review of the environmental performance of the storage systems is also conducted, identifying potential trade-offs between sustainability and energy storage efficiency. The results highlight the potential of PV systems integrated with optimized energy storage technologies to enhance the energy efficiency, sustainability, and cost-effectiveness of near-zero energy buildings (NZEBs).
Keywords: Photovoltaic panels; Lithium-ion battery; Lead acid batteries; Flywheel energy storage; Solar energy; Exergy efficiency; Net zero building; HEAT; Engineering